A Novel Approach to Reduce the Unicast Bandwidth of an IPTV System in a High-Speed Access Network - El Hassane Khabbiza; Rachid El Alami; Hassan Qjidaa (International Journal of Digital Multimedia Broadcasting)
Channel change time is a critical quality of experience (QOE) metric for IP-based video delivery systems such as Internet Protocol Television (IPTV). An interesting channel change acceleration scheme based on peer-assisted delivery was recently proposed, which consists of deploying one FCC server (Fast Channel Change Server) in the IP backbone in order to send the unicast stream to the STB (Set-Top Box) before sending the normal multicast stream after each channel change. However, deploying such a solution will cause high bandwidth usage in the network because of the huge unicast traffic sent by the FCC server to the STBs. In this paper, we propose a new solution to reduce the bandwidth occupancy of the unicast traffic, by deploying the FCC server capabilities on the user STB. This means that, after each channel change request, the STB will receive the unicast traffic from another STB instead of the central server. By using this method, the unicast traffic will not pass through the IP network; it will be a peer-to-peer communication via the Access Network only. Extensive simulation results are presented to demonstrate the robustness of our new solution.